EP1337 A primary extended cytoreductive surgery for ovarian cancer: total abdominal hysterectomy and bilateral salpingo-oophorectomy, total omentectomy, total peritonectomy, bilateral diaphragm stripping, cholecystectomy, total colectomy, splenectomy, bilateral pelvic-paraaortic lymphadenectomy, dissection of porta hepatis, liver metastasectomy, and bilateral cardiophrenic lymphadenectomy. (1st November 2019) - Taskiran, C; Vatansever, D; Eraslan, A; Giray, B; Misirlioglu, S; Balik, E; Kumcular, T; Arvas, M
Abstract : Introduction/Background: Ovarian cancer is the leading cause of death among gynecological malignancies. Primary cytoreduction for ovarian cancer is associated with significantly improved survival. We aimed to present a primary extended cytoreduction performed in this video. Methodology: A 37 years-old woman was admitted with abdominal swelling and pelvic pain. Pelvic examination revealed out ascites and bilateral adnexal masses. MRI showed 11-cm right adnexal mass, 7-cm left adnexal mass, omental cakes, disseminated peritoneal implants, liver metastases, and enlarged lymph nodes in the right obturator fossa. Total abdominal hysterectomy, bilateral salpingo-oophorectomy, total omentectomy, total peritonectomy, bilateral diaphragmatic stripping, total colectomy, splenectomy, bilateral pelvic-paraaortic lymphadenectomy, cholecystectomy, dissection of the porta hepatis, liver metastasectomy, and transabdominal cardiophrenic lymph node dissection were performed as a part of maximal primarily cytoreduction. Results: We did not encounter any grade 3 or 4 adverse event in post-operative period. Conclusion: Primary cytoreduction for ovarian cancer with no residual disease is a major impact on survival. The management of this condition should be performed with expert multidisciplinary teams in gynecological oncology. Disclosure: Nothing to disclose